METHODS OF SOLVING NON-STANDARD MATHEMATICAL PROBLEMS - Mukhtorbek Rokhimovich Yusupov (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents convenient ways to solve some non-standard problems that appear in science olympiad problems for mathematics.